Unit of Competency for Development of Occupational Standards to Align Workforce Competence with Labor Market Demands and Educational Outcomes - Surono Surono (PT Publikasiku Academic Solution, 2025)
This study addresses the gap between education systems and labor market demands by developing a validated unit of competency titled “Research and Develop Occupational Standards.” Using a Research and Development (R&D) methodology alongside the Regional Model Competency Standards (RMCS), the study generated three main outcomes: a validated competency unit, a replicable model integrating job classifications, occupational standards, curriculum, and certification, and five policy recommendations for integrating these standards into National Qualification Frameworks (NQFs). The research emphasizes the need to transition from experience-based recruitment to skills-based hiring, addressing the global challenge where only 34% of employers apply competency-focused practices (World Economic Forum, 2023). The study’s findings also contribute to aligning educational outcomes with labor market needs, thereby enhancing employability and ensuring that qualifications remain relevant amidst the digital transformation and the growing demand for sustainability-related skills. The study’s implications are far-reaching, providing a framework for policymakers, education providers, and industry stakeholders to improve workforce competency and support lifelong learning. Future research should explore digital tools, such as AI and blockchain, to enhance the scalability and real-time responsiveness of labor market skills and qualifications.